ANALISIS PENGARUH FAKTOR PERTUMBUHAN EKONOMI, PENDIDIKAN, DAN PENGANGGURAN TERHADAP KETIMPANGAN DISTRIBUSI PENDAPATAN DI INDONESIA - Aufa Nadya; Syafri Syafri (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2019)
This study is analyze the impact of economic growth, education and unemployment on the inequality of income distribution and see which provinces contribute the most to income inequality in Indonesia. This study used Panel regression analysis with the Eviews 8 analysis tool. The data used in this research are Gini ratio, GDRP growth rate, mean of school duration, and open unemployment rate from 33 Provinces within 2007 to 2016 (330 observations). The results show that economic growth has no impact on income inequality, at the same time education has a positive impact and unemployment has a negative impact on income inequality in Indonesia. The results show that Banten is a province with the highest level of income inequality.